An Integrative Network Modeling Approach to T CD4 Cell Activation - Martínez-Méndez, David; Villarreal, Carlos; Mendoza, Luis; Huerta, Leonor (Frontiers in Physiology, 2020)
The adaptive immune response is initiated by the interaction of the T cell antigen receptor/CD3complex (TCR) with a cognate peptide bound to a MHC molecule. This interaction, along withthe activity of co-stimulatory molecules and cytokines in the microenvironment, enables cells toproliferate and produce soluble factors that stimulate other branches of the immune responsefor inactivation of infectious agents. The intracellular activation signals are reinforced, amplifiedand diversified by a complex network of biochemical interactions, and includes the activity ofmolecules that modulate the activation process and stimulate the metabolic changes necessaryfor fulfilling the cell energy demands. We present an approach to the analysis of the main earlysignaling events of T cell activation by proposing a concise 46-node hybrid Boolean model of themain steps of TCR and CD28 downstream signaling, encompassing the activity of the anergyfactor Ndrg1, modulation of activation by CTLA-4, and the activity of the nutrient sensor AMPKas intrinsic players of the activation process. The model generates stable states that reflectthe overcoming of activation signals and induction of anergy by the expression of Ndrg1 in theabsence of co-stimulation. The model also includes the induction of CTLA-4 upon activation andits competition with CD28 for binding to the co-stimulatory CD80/86 molecules, leading to stablestates that reflect the activation arrest. Furthermore, the model integrates the activity of AMPK tothe general pathways driving differentiation to functional cell subsets (Th1, Th2, Th17, and Treg).Thus, the network topology incorporates basic mechanism associated to activation, regulationand induction of effector cell phenotypes. The model puts forth a conceptual framework for theintegration of functionally relevant processes in the analysis of the T CD4 cell function.